Faktor yang Mempengaruhi Rendahnya Minat Pasangan Usia Subur (PUS) dalam Penggunaan KB IUD: Literatur Review - Ulfah, Alfiyah; Sutrisminah , Emi (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
Regulating birth spacing and improving family welfare are two goals of family planning, which aims to strike a balance between the population's demands.  The purpose of this research was to determine why so few couples of reproductive age use intrauterine devices (IUDs).  The study relied on a literature review methodology and used the PICO search strategy to systematically search the following databases: PubMed, Science Direct, and Google Scholar.  The final product was a set of seven articles written in Indonesian and five pieces written in English that fulfilled the inclusion criteria.  The tiny number of 9.36% of Indonesians who utilize intrauterine devices (IUDs) is due to a number of reasons, including but not limited to: age, knowledge, socioeconomic status, education, culture and religion, parity, side effects, and husband support.